PREVALENCE OF GENDER-BASED VIOLENCE AGAINST WOMEN IN KIRU TOWN COUNCIL IN ABIM DISTRICT. A CROSS-SECTIONAL STUDY. - Okello , Benson Jerald; Matte, Florence Rita; Modi, Derick; MALINGA , JOSEPH; Owilli, Emmanuel Tonny; Apio, Maureen; Kayizzi, Julius (SJ Insights, 2024)
Background This study assessed the prevalence of GBV amongst women (15-49) years of Kiru town council in Abim district. Methodology The study adopted a sectional study design using quantitative research methods. Multi-stage sampling was used for a sample size of 152 women of reproductive age. Data was collected using pre-piloted, structured interview-administered questionnaires. The data was analyzed using the SPSS version 23 software in two levels of Uni-variate and bi-variate and the analysis was conducted using descriptive and regression analysis. Results The prevalence of gender-based violence among women (15-49) years of Kiru town council was 30.3%. The factor socio-demographic factor married(c0R; 0.034, 95% CI, 0.003-0.335, p-value= 0.004), those who were emotionally abused(c0R; 0.345, 95% CI, 0.168-0.709, p-value= 0.004), sexually abused (cOR; 0.314, 95% CI, 0.153-0.646, p-value=0.002), those who experienced their last episode of GBV within (1-5) years(cOR; 2.556, 95% CI, 1.058-6.171, p-value=0.037), those who reported their cases to the counsellor(c0R; 9.205, 95% CI,1.190-71.176, p-value= 0.033), police(c0R; 0.384, 95% CI, 0.180-0.822, p-value= 0.014) and those who lacked trust of benefits in the services available (c0R; 2.651, 95% CI,1.067-6.389, p-value= 0.038) were significantly associated with the prevalence of GBV. The prevalence of physical violence was 52.7%, sexual violence was 43.4% and emotional violence was 34.9%. 12.5% of the respondents did not report their cases to any service and amongst those who reported their cases, 32.9% faced stigma. Conclusion 30.3% of women (15-49) years have ever experienced GBV in their lifetime. This shows that there’s a need to carry out health education in Kirutown council to create more awareness about the dangers of GBV against women (15-49) years. Recommendation Community members should speak out against harmful gender norms, stereotypes, and attitudes that perpetuate GBV and also challenge sexist language, jokes, and behaviors in their personal and professional circles.